Caesium and Strontium Isotopes Concentrations in Some Enviromental Samples and Gamma Radiation Fields in (Hanoi, Haiphong and Viettri) Cities, North Vietnam, 1980 - 1990 - Uyen, Dang Huy (VNU Journal of Science: Mathematics - Physics, 2003)
Abstract